Investigations of LHCD induced plasma rotation in Tore Supra. (16th October 2015) - Chouli, B; Fenzi, C; Garbet, X; Bourdelle, C; Sarazin, Y; Rice, J; Aniel, T; Artaud, J-F; Baiocchi, B; Basiuk, V; Cottier, P; Decker, J; et al.
Abstract: Theoretical investigations are performed in order to explain the plasma rotation increments induced by lower hybrid current drive (LHCD) in Tore Supra and the results are compared to the experimental observations. The intrinsic toroidal rotation is governed by several mechanisms in concert. The impact of the LHCD on each involved mechanism is analyzed. The neoclassical toroidal rotation is always in the counter-current direction. The toroidal diamagnetic velocity is of the order of the experimental toroidal velocity. At high plasma current the rotation evolution in the lower hybrid (LH) phase is controlled by the neoclassical friction force due to the trapped ions in banana trajectories through the toroidal diamagnetic velocity. This force results in the counter-current increment as observed in the experimental measurement of toroidal rotation. At low plasma current the rotation is dominated by momentum turbulent transport when the LH waves are applied. The Reynolds stress grows strongly compared to the high plasma current case and acts as a co-current force through its residual stress contribution. Momentum transport simulations are also performed with CRONOS (Artaud et al 001 ) in order to assess the rotation increments induced by LHCD.